Viral in Social Media: the Viralor and the Viralee - Nazim Abdullah, Raja; Azhari Azman, Mohamed Nor (International Journal of Psychosocial Rehabilitation, 2019)
Purpose. The purpose of this paper is to look into different approaches to study on information sharing platforms in social media. Social media has become imperative and pervasive social interaction between people all over the world and perhaps the most popular communication channels for all-aged Internet users. Design/methodology/approach Academic literatures indicate social media users receive and sharing enormous information using Internet-based application technologies such as computer, hand phone, email etc. are closely tied to online social networks. Most of the viral shared around the world arouse peoples’ conceit toward Viralee for some purposes. Viral are poised to become the chain of information, embedded communication features of the world around us. Findings Analysis from empirical evidence proves that unrestraint of information processes for social media users signify the impact of information sharing paradigm. The Viralor, is creator or primal source of information chain who create the viral whilst Viralee is a form of human being, or object, or institution, or phenomena, to be viral. Viral are divided into two categories; positive viral and negative viral. Originality/value This paper contributes to the theory on the implications of occurrence Internet users on social media to the contingency of information chain networks. The paper draws intention to the implication of information sharing behavior on social media.